ANALISA HERMENEUTIK KESEJAJARAN YAKOBUS 5:14 DAN MARKUS 6:13 TENTANG BERDOA DAN PENGOLESAN MINYAK SEBAGAI IMPLEMENTASI PELAYANAN - Tri Endah Astuti; Aska Pattinaja (Sekolah Tinggi Teologi Arastamar Bengkulu, 2025)
The book of James is one of the epistles of Am in the New Testament. There are parallels in the narrative context and purpose told in James 5:14 with Mark 6:13. Based on the results of the literature study, it was found that the research conducted specifically in the context of James 5:14 focused more on the thematic of prayer and the application of oil, without looking at the parallels and hermeneutic analysis. The juxtaposition of these two verses is an interesting thing that this article examines, using a qualitative method based on a hermeneutic exegesis approach, as an implementation in doing ministry. This article finds that there are three important standards in ministry, namely, first, choose the right method of ministry based on biblical references in accordance with the example of Jesus. James recommend this method to the elders of the church, because this is a legacy of ministry that he learned from the example of Jesus; second, the ministry of prayer and the application of oil is only a method that is applied contextually, but ministers must direct the main focus of healing only to Jesus, to avoid the cult of individuals who serve and to the anointing oil; third, the service method of prayer and the application of oil must be carried out by ministers who are specialized to do so, to be ethical and responsible. This article can be a reference for ministers and church leaders, who are engaged in the service of God's people.